Criticality of raw materials - a clarification and redefinition of the term worldwide - Castro-Sejin, Alvaro; Mammadli, Anvar; Barakos, George (AusIMM, 2023)
Though not new in the literature, the term criticality of raw materials has become prevalent in recent years, referring to the importance and vulnerability of resources in various industries and technological advancements. However, criticality is perceived differently worldwide and is influenced by many more parameters than the supply disruption risk. This work comprehensively analyses the definition and determination of criticality for minerals and metals worldwide. The review examines the parameters used to assess criticality, considering factors such as supply and demand dynamics, geopolitical risks, market fluctuations, national security, environmental, and social and cultural considerations. The aim is to offer an in-depth understanding of the diverse conditions and perceptions surrounding criticality through a detailed review of research articles, technical reports, and industrial and governmental publications. The authors explore how different regions, countries and stakeholders define and prioritise critical raw materials based on their specific economic, political, environmental, social, and cultural contexts. By synthesizing the findings, this study aims to establish a more complete and broad understanding of the multifaceted nature of criticality assessment. It highlights the importance of simultaneously considering various parameters and factors when evaluating the criticality of raw materials. The culmination of these discussions will aid in developing a unified global term for raw materials criticality. The outcomes of this research will improve informed decision-making, resource management strategies, and the development of sustainable practices in the critical minerals and metals industry.